Exploring the Experiences of Women with ADHD in Professional Settings: A Qualitative Study - Moradi, Arezou; Rootivand Ghiasvand, Zahra (KMAN Counseling & Psychology Nexus, 2025)
Attention-Deficit/Hyperactivity Disorder (ADHD) in women is often underdiagnosed and understudied, particularly in professional settings. This study aims to explore the experiences of women with ADHD in the workplace. This qualitative study was conducted in Tehran, Iran, using a phenomenological approach. Data were collected through semi-structured interviews with 19 women diagnosed with ADHD who were currently employed in various professional settings. Theoretical saturation guided the sample size. Interviews were transcribed, translated, and analyzed using NVivo software for thematic analysis. Four main themes emerged from the data: Challenges in the Workplace, Coping Strategies, Perceptions of Workplace Support, and Impact on Professional Identity. The challenges included difficulties with time management, attention and focus, organizational skills, communication issues, and high levels of stress and anxiety. Coping strategies encompassed personal techniques, professional support, adaptive technologies, self-care practices, social support, and environmental modifications. Perceptions of workplace support varied, with positive experiences linked to understanding supervisors, inclusive organizational policies, and professional development opportunities. The impact on professional identity included feelings of inadequacy, imposter syndrome, and the recognition of ADHD-related strengths. The study highlights the unique challenges faced by women with ADHD in professional settings and underscores the importance of tailored support and increased workplace awareness. By implementing supportive measures and creating inclusive environments, organizations can enhance the job satisfaction, productivity, and well-being of women with ADHD, enabling them to fully realize their professional potential.